The Effects of HIV/AIDS on Human Resource Operations in the Hospitality Industry. "A Case Study of the Coastal Region of Kenya - Nzioka, Alice Mueni (My University, 2007)
There are about 39.5 million people globally living with the human immunodeficiency virus (HIV). Sub-Saharan Africa has the highest prevalence with just over 24 million people who are HIV positive. Kenya has approximately 1.3 million people infected. The International Labor Organization estimates that 28 million workers are HIV positive. Tourism is the second largest industry in Kenya, providing jobs, tax, revenue, and foreign currency to this country. There is no study in Kenya on the effects of HIV/AIDS in the hospitality industry. The purpose of this study was to examine the extent to which HIV/AIDS has affected the human resource operations in the hotel sector in the Coast region of Kenya. The study examined HIV/AIDS related absenteeism, loss of productivity, labor costs, and labor turnover, and their effects on human resource operations in the hotel sector. Stratified random sampling was employed to select 57 hotels out of the 76 classified hotels in the region. Questionnaire, focus group discussion and a retrospective analysis of document were used for data collection. The Spearman Rank Correlation Coefficient, the Pearson Correlation Coefficient and the Chi-Square were used. The results were presented in charts, frequency tables, percentages, and histograms. The Spearman Rank Correlation Coefficient indicated a positive relationship between absenteeism and labor costs. The Pearson Correlation Coefficient indicated a positive relationship between HIV/AIDS related heath care costs and hotels clinic attendance. Significance was accepted at p < 0.05. The Chi- Square Test indicated a X'calculated > X2 tabulated at 95% confidence level and hence rejecting the hypotheses. The results showed that absenteeism due to morbidity and mortality of HIV/AIDS related illnesses was significant. Further operational costs rose from Ksh. 532,000 in 2000 to Ksh.819, 000 in 2004. The death rate rose by 2% between 2000 and 2004 while funeral costs rose by 2% within the same period. Employee absenteeism rose from 1,560 labor days in 2000 to 3,446 labor days in 2004. Hotels experienced attrition in skills, increase in labor costs as well as reduced performance levels. All these affected productivity and profits. From the findings of this study it is concluded that HIV /AIDS appears to have impacted negatively on the hotels in terms of absenteeism of workers, loss of skills and knowledge, increase in operating costs as well as reduced performance levels. It is recommended that all hotels should have well-elaborated HIV IAfs prevention programs and concerted mitigation strategies. The hotels should develop HIV/AIDS workplace policies and intensify awareness and prevention campaigns.